Are information disclosure mandates effective? Evidence from the credit card market - Alan Elizondo; Enrique Seira (Banco de México, 2014)
Consumer protection in financial markets in the form of information disclosure is high on governments agendas, despite the fact that the empirical evidence on its effectiveness is scarce. To measure the impact of Truth-in-Lending-Act-type disclosures on default and indebtedness, as well as of debiasing warning messages and social comparison information, we implement a randomized control trial in the credit card market for a large population of indebted cardholders. We find that providing salient interest rate disclosures has no effect, while social comparisons and debiasing messages have only a odest effect. Other types of disclosures discussed in the paper could have larger effects.
Keywords: D12; D14; D83; G02; G21; G28; 330; credit cards; information disclosure; truth in lending; Mexico